The Prevalence of Depression in Older Turkmen Adults in 1389 - Azize Gharanjik; Farahnaz Mohammadi Shahbolaghi; Gholamreza Ansari; Farid Najafi; Shadi Ghaderi; Kazem Ashrafi; Negin Taheri; Robab Sahaf (University of Social Welfare & Rehabilitation Sciences, 2011)
Objectives: The elderly population in the world is growing and, by 2050, it is expected to exceed 20% of the world's population size, with the majority living in developing countries. Psychological disorders are among the most important problems in elderly people. There are some barriers in the elderly with specific race and ethnicity that can lead to difficulty in detection and interpretation of psychological and mood disorders, for instance language and lower education levels. In this survey, the prevalence of depression in elderly Turkmen over 60 years of age was measured based on standard tests. Methods & Materials: This was a cross-sectional study conducted on 300 community- dwelling Turkmen over 60 years of age without cognitive impairment. Individuals were randomly selected using cluster sampling. In this research, questionnaires containing demographic information and standardized questionnaires of depression in the elderly (GDS15) were used and completed during interviews. Results: Data analyses showed that the mean depression score was 4.31±3.353, with 20 percent of participants experiencing mild depression, 10 percent moderate depression, 3 percent severe depression, and 67 percent remaining asymptomatic. The mean age for men and women was 69±7.06 and 67±6.48, respectively. Conclusion: Depression is a significant problem in public health. The prevalence of moderate and severe depression among older Turkmen adults is lower or similar to rates found in other research in Iran. Given the prevalence of mild depression, correct planning for early diagnosis and treatment is necessary. Determining depression-influencing factors is recommended.